2015
DOI: 10.1097/mca.0000000000000252
|View full text |Cite
|
Sign up to set email alerts
|

Association between serum galectin-3 levels and coronary atherosclerosis and plaque burden/structure in patients with type 2 diabetes mellitus

Abstract: Galectin-3 is a novel, promising biomarker that may help identify type 2 diabetic patients who may require early CAD intervention because of the potential risk of coronary atherosclerosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
34
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 23 publications
5
34
1
1
Order By: Relevance
“…Galectin-3 levels were correlated with BMI, hs-CRP, and the total number of plaques. Older age, smoking, high hs-CRP, and high LDL-cholesterol concentrations, in addition to galectin-3, were predictors of coronary atherosclerosis in patients with type 2 DM [10]. In our study, consistent with the findings of this study, BMI, hs-CRP, and the total number of plaques were significantly positively correlated with galectin-3.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Galectin-3 levels were correlated with BMI, hs-CRP, and the total number of plaques. Older age, smoking, high hs-CRP, and high LDL-cholesterol concentrations, in addition to galectin-3, were predictors of coronary atherosclerosis in patients with type 2 DM [10]. In our study, consistent with the findings of this study, BMI, hs-CRP, and the total number of plaques were significantly positively correlated with galectin-3.…”
Section: Discussionsupporting
confidence: 82%
“…Moreover, de Boer et al [9] reported that galectin-3 level was an independent predictor of all-cause and cardiovascular mortality in the general population, independent of other cardiovascular risk factors. A significant relationship between serum galectin-3 concentrations and the total number of coronary plaques and the macrocalcified plaque structures, as detected by CCTA, of patients with type 2 DM was demonstrated in a study by Ozturk et al [10]. Galectin-3 levels were correlated with BMI, hs-CRP, and the total number of plaques.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…72 In diabetic patients, galectin-3 concentrations were significantly elevated in subjects with coronary artery disease and associated with the formation of diseased vessels and plaques. 74 Darrow et al found that mice developed hyperglycemia since week 2 of high-fat diet feeding, which was indicated by a threefold increase in homeostasis model assessment for insulin resistance (HOMA-IR) index and a 1.5-fold decrease in Akt activation. The authors also found increased galectin-3 expression in endothelial cells as well as circulating galectin-3 in high-fat diet-fed mice, suggesting that galectin-3 plays a role in the vascular response in DM (Table 1).…”
Section: Galectin-3 In Metabolic Disease Pathogenesismentioning
confidence: 99%
“…In clinical studies, circulating galectin-3 was higher in type 2 DM patients [71][72][73][74] and thought to be a risk factor for vascular complications, such as heart failure, nephropathy, peripheral artery disease, and other vascular complications. 71 Patients with galectin-3 level 25 ng/mL exhibited a 11.4-fold higher risk of microvascular complications (retinopathy and/or nephropathy) and a 8.5-fold increased risk of macrovascular complications (myocardial infraction, angina pectoris, cerebrovascular event, and peripheral artery disease) compared to patients with galectin-3 level 10 ng/mL.…”
Section: Galectin-3 In Metabolic Disease Pathogenesismentioning
confidence: 99%